2005
DOI: 10.1177/1066480705278729
|View full text |Cite
|
Sign up to set email alerts
|

The Gendered Nature of Sexual Scripts

Abstract: Social scripting theory points to the fact that much of sexual behavior seems to follow a script. Similar to scripts that stage actors use to guide their behavior, social scripts instruct members of a society as to appropriate behavior and the meanings to attach to certain behaviors. In Western cultures, scripts for sexual activity are markedly different for males and females. In this article, the goals are to provide (a) an introduction to social scripting theory, (b) an exploration of the ways and potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
262
1
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(290 citation statements)
references
References 19 publications
(19 reference statements)
10
262
1
17
Order By: Relevance
“…According to these authors, women tend to focus on their own weight and body and therefore to become fearful of developing weight problems, while men pay attention to slimness in other's bodies to appreciate it or to criticize it, as in the case of obese people. In other words, men judge bodies and women are judged by their bodies (Wiederman, 2005). As a matter of fact, it has been found that men report greater antifat attitudes than women (Crandall, 1994).…”
Section: Internalization-externalization Hypothesismentioning
confidence: 99%
“…According to these authors, women tend to focus on their own weight and body and therefore to become fearful of developing weight problems, while men pay attention to slimness in other's bodies to appreciate it or to criticize it, as in the case of obese people. In other words, men judge bodies and women are judged by their bodies (Wiederman, 2005). As a matter of fact, it has been found that men report greater antifat attitudes than women (Crandall, 1994).…”
Section: Internalization-externalization Hypothesismentioning
confidence: 99%
“…Masculine gender roles have long dictated power, general independence, assertiveness and exploration. Whereas feminine gender roles command ideals of behavioural restraint and personal control (Lippa 2001;Oliver and Hyde 1993;Wiederman 2005).…”
Section: Review Of the Literature Escort Services And The Internetmentioning
confidence: 99%
“…face-to-face meetings. Codes were collapsed into themes informed by Wingood's focus of Connell's TGP on the powerless of AA women in sexual decision making [44][45][46]66] and Stephen and Phillip focus on female's sexual script development research of AA women [36,[50][51][52][53][54][55][56][57][58][59][60]. The research team then conducted a frequency analysis on emerging themes using NVIVO11 and Microsoft Excel software.…”
Section: Purposementioning
confidence: 99%
“…Stephens and Phillips' focus of females' sexual script development research with AA women explores ways culture shapes perception, expression of appropriate and socially acceptable sexual behavior, individual level expectations, and experiences of behaviors that occur in series [49] within a population at high risk for HIV [36,[50][51][52][53][54][55][56][57][58][59][60]. The SST articulates the way sexual scripts provide instructions (i.e., a roadmap) for clarifying the intention and meaning of sexual cues and responding to them, which in turn informs how men and women behave in sexual situations [50,51,[60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation